Coronary Artery Disease Patients have an Abnormally High Frequency of Aberrant Lipid Profiles - Naveed Yaqoob, Muhammad Saeed Afridi, Muhammad Ahmad Raza Butt, Muhammad Suleman Khan, Fahad Khalid, Mujeebullah Tareen, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The study was conducted with the aim to estimate the frequency of abnormal lipid distribution in patients with coronary artery disease. Study design: cross sectional, comparative study Place and duration: This study was conducted at Rawal Institute of Health Sciences, Pakistan and Rashid Latif Medical College Lahore in the period from April, 2022 to September, 2022. Methodology: A total of one hundred and thirty two participants of both genders were selected as the study population on obeying the inclusion and exclusion criteria of the study. Participants were distributed in the two comparable groups with 92 CHD patients in case group and 40 healthy people in control group. An informed written consent was signed by all the participants to record patients detailed demographics age, sex and body mass index. Blood sample was taken from each participant to analyze the lipid profile. Frequency of lipid profile (cholesterol, triglycerides, HDL-C, LDL-C and VLDL) were measured using commercially available kits. The entire data was analyzed via SPSS 24.0. Results: Among the total participants, the majority were males (75.8%) while females were (24.2%). Most of the participants were aged > 60 (36.4%), while participants had BMI >25kg/m2 were (56.8%). Majority of the participants were married (64.4%). In the case group, mean TC(>200mg/dl) was 263.91± 23.73, mean TG(>150mg/dl) was 210.71± 42.17, mean HDLc(<40mg/dl) was 47.44±5.91 and mean LDLc(>130mg/dl) was 99.88±20.73 respectively. Case group with CAD showed the majority of males (70.65%) while 29.35% were females. Conclusion: In the given study, it was found that the frequency of abnormal lipid profile (TC, TG, HDL-C and LDL-C) concentrations were considerably higher in the patients with coronary artery disease. Total cholesterol and serum triglyceride were significantly higher than LDL-C and HDL-C. Moreover, males were more likely to had lipid profile abnormalities than females. Keywords: lipid profile, abnormalities, CAD, frequency